(untitled) (Dristikon: A Multidisciplinary Journal, 2020)
This paper seeks to examine the productivity of Tax Revenue (TR) in the Nepalese economy. It, therefore, analyzes the impact of TR on GDP in aggregate level. This study adopts explanatory research design and attempts to determine the relationship between TR and the GDP. Exchange rate, market capitalization money supply and government spending being the intervening variables included in the model. In order for the specification of a model of co integrated regression model with a time series data of the variables are employed for the study period of 20 years, from 1999/2000 to 2018/19. The values of all the variables are converted into real price (constant price) by GDP deflator. The GDP deflator and CPI year 2013/14 have been assumed equivalent to the base year 2013/14 according to Nepalese fiscal year. Since it is observed that residuals are not normally distributed, autocorrelation and multi-co linearity problem in the model, it is necessary to improve the non-normal distribution, autocorrelation and multi-co linearity problem in the model. Therefore, the data are transposed into first difference and run the model with error correction model (ECMt-n). The R2 shows that the explanatory power of the model, indicating that the variation of GDP is explained to the extent of 81 percent variation of the independent variable included in the model. The estimated coefficient of TR in error correction model shows that one percent point rise in TR has led to0.17645 percent point increase in real GDP in short run, whereas it is found 0.21364 percent point in the long-run. This is supported by (World bank, 2003, 2007, 2018) using a large sample of developing countries observed over the period 1980-2006, and even after factoring in the endogeneity of tax revenue.